Neospora caninum EN CAMÉLIDOS SUDAMERICANOS PERUANOS - Chávez V., Amanda (2002)
The research group at the Veterinary Faculty of San Marcos University and Universidad Complutense, Madrid, Spain is involved in an study aiming to determine the presence of antibodies against Neospora caninum in South American camelids and its possible role in abortion. Preliminary data has shown that 42.4% alpacas and 18.4% llamas from small-farmer communities in the highlands of Peru were positives to N. caninum.